Exploring new feedback practices paradigm in higher education: students’ perspectives - Genisa, Marlina Ummas; Rizal, Haryanti Putri; Hasri, Hasri; Agussalim, Andi (International Journal of Evaluation and Research in Education (IJERE), 2025)
Feedback has recently shifted from being received to being an interaction process, raising considerable interest among educators. This study aims to examine whether current feedback practices in higher education have led to active student interaction processes, and how individual and contextual factors are considered in practice based on gender and university perspectives. An online questionnaire was used to collect data from 418 students from three Indonesian universities, Universitas Negeri Makassar (UNM), Universitas Muhammadiyah Palembang (UMP), and Universitas Sulawesi Barat (USB). The data was analyzed descriptively-quantitatively. Results indicate that current feedback practices do not adequately direct students to actively participate in the processing feedback. The feedback received is dominated by general feedback (UNM and USB), while detailed and discussed feedback is generally received by UMP students. Additionally, the expected and effective feedback obtained the same pattern that individuals and groups must interact which is in line with the new paradigm. The results also showed the ideal time for providing feedback is 5-10 days for various types of assignments and 15-20 days for theses. These results provide educators with information on strategies and approaches in feedback practices that are relevant and effective in enhancing student learning based on the new paradigm.